Field Study on Oscillating Pontoon Wave Energy Converter (WEC) Performance in Nearby Muarabaru, North Jakarta - Abdul Hamid; Mardani Mardani; Dede Rukmayadi (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2025)
Abstract Two-thirds of Indonesia's territory is sea waters with different wave heights according to local geographical conditions. And only with the mastery of technology, wave energy can be converted into electrical energy which is priceless. This paper aims to determine the performance of a wave energy converter (WEC) device based on a damped forced vibration system. The WEC set consists of a marine structure measuring 3.00 meters high, 2.00 meters wide, and 2.00 meters long; a two-dimensional heaving-pitching gearbox as a power take-off (PTO) and a pontoon type “H” beam measuring 2.96 meters long, 0.92 meters wide. The research was conducted by field testing on a 50-meter coastline measured from the low tide shoreline of nearby Muarabaru, North Jakarta, for 24 hours from high tide to the next which is done every 6 hours. The research results show that: The output power generated by the heaving motion is = 36.25 Watts, The efficiency value due to heaving = 25.87% The output power generated by the pitching motion is = 37.9 Watt, The efficiency value due to pitching = 27.30% Keywords: damped forced vibration system; performance of WEC; pontoon type